ASSESSMENT OF CLINICAL INDICATORS FOR ANAEMIA IN THE ALGORITHM FOR INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS (IMCI), WAD MEDANI PAEDIATRICS HOSPITAL, SUDAN 2001-2002 - Abdel Rahman, Samira Hamid; Idris, Ali Ahmed; Yousif, Bakri; M. Haroon, Huda (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
The object of this study was to assess IMCI clinical indicators used for the assessment and classification of anaemia in underfines. A total of 500 children (aged 2-59 month)were selected by systematic random method from sick children attending to the outpatient department of the paediatrics hospital in Wad Medani, Sudan. The study doctors obtained a standardized history and carried out IMCI standard case management. Heamoglobin concentration and blood smear for malaria parasites were then performed for every enrolled child. Using the WHO Hb levels to diagnose anaemia, the sensitivity and specificity of IMCI guidelines to classify anaemia were examined. The sensitivity and specificity of “ no palmar pallor” as a predictor of no anaemia were 60% and 50% respectively; and of  “some pallor” as predictor of mild-moderate anaemia were 44%, 60%; whereas  “severe pallor” showed a sensitivity of 52% and a very high specificity for 90% on detecting children with severe anaemia. Palmar pallor was not significantly associated with the presence of malaria as detected by a positive blood film for plasmodium falciparum. The study thus provides technical validation of IMCI algorithm for the assessment of anaemia. However, it did not provide proof of a significant association between palmar pallor and malaria, in the presence of fever.